Plug in 2 for x. f(20=2-51 = -49
Answer:
Positive, because the products (3) × (−3) and (−2) × (4) are negative and the product of two negative numbers is positive.
Step-by-step explanation:
Since 1 * -1 = -1, and -1 * -1 = 1, the product of opposite signs produces negative numbers while the product of same signs produces positive numbers. So the product of 1 * 1 * 1 * -1 = -1, while -1 * -1 * -1 * -1 = 1.
Hello from MrBillDoesMath!
Answer:
3 ( -x + 2) is the factorization; 3 is the common factor
Discussion:
Each term in
-3x + 6 has 3 as a factor so the factorization is
3 ( -x + 2)
Thank you,
MrB